2014
DOI: 10.1128/aem.03397-13
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of Pinoresinol into Matairesinol by Use of Recombinant Escherichia coli

Abstract: Lignans, a class of dimeric phenylpropanoid derivative found in plants, such as whole grains and sesame and flax seeds, have anticancer activity and can act as phytoestrogens. The lignans secoisolariciresinol and matairesinol can be converted in the mammalian proximal colon into enterolactone and enterodiol, respectively, which reduce the risk of breast and colon cancer. To establish an efficient bioconversion system to generate matairesinol from pinoresinol, the genes encoding pinoresinol-lariciresinol reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, exactly defining the effectiveness of such conversion, according to the type of lignan molecule, is a difficult task due to the inconsistency of results. Nonetheless, both in vitro [19,22] and in vivo [23] studies reported that the catabolic transformation of SECO and MAT was observed to be greater than LAR, SYR, PINO, and sesamin and, in turn, that aglycones are more efficiently metabolized than diglucosylated derivatives. Except for MAT that generates EL but not ED, the contribution of each plant lignan to the whole pool of ED and EL is not entirely clear [19].…”
Section: Intraindividual and Interindividual Variability In The Convementioning
confidence: 99%
See 1 more Smart Citation
“…However, exactly defining the effectiveness of such conversion, according to the type of lignan molecule, is a difficult task due to the inconsistency of results. Nonetheless, both in vitro [19,22] and in vivo [23] studies reported that the catabolic transformation of SECO and MAT was observed to be greater than LAR, SYR, PINO, and sesamin and, in turn, that aglycones are more efficiently metabolized than diglucosylated derivatives. Except for MAT that generates EL but not ED, the contribution of each plant lignan to the whole pool of ED and EL is not entirely clear [19].…”
Section: Intraindividual and Interindividual Variability In The Convementioning
confidence: 99%
“…In another study, after the daily intake of 0.3 g flaxseed/kg body weight by healthy man for 1 week, the mean serum concentration of ED and EL increased 10-fold compared to baseline until reach 20 and 60 nM, respectively, but not all the participant responded to the same form since ED increased in all participants while EL remained unchanged in two subjects [26]. Many dietary interventions including pharmacokinetic studies in human [11] and animals [23,24] and prolonger plant lignan supplementation in human [13] have presented the mean values of ED and EL or only EL in biofluids before and after the intervention. Still, they have not discriminated among categories of different metabolic responses losing the opportunity to gather data to define how individuals respond to plant lignans supplementation as proposed by other authors [15].…”
Section: Intraindividual and Interindividual Variability In The Convementioning
confidence: 99%
“…Each bioconversion reaction was prepared with a total volume of 250 ll that contained 20 mM Tris buffer (pH 8.8), 5 mM DTT, 4 mM NAD, and 165 lM (-)-secoisolariciresinol [29]. The reaction was incubated at 30°C for 2 h. Each sample was extracted 39 with 300 ll ethyl acetate (EtOAc), the combined EtOAc extract was dried under N 2 (g), and the precipitate reconstituted in 200 ll methanol (MeOH) for HPLC and LC-MS analyses.…”
Section: Bioconversion Assaymentioning
confidence: 99%
“…Generally, the expression temperature and duration substantially influenced CYP719A23 expression (Table S13). Although the highest expression of CYP719A23 was achieved at 20 °C, 25 °C was chosen as a compromise for establishing the reaction cascade with regard to the optimal expression conditions for FiPLR and PpSDH reported elsewhere and confirmed in our previous study …”
Section: Resultsmentioning
confidence: 84%